The Making of the Mexican Border : The State, Capitalism, and Society in Nuevo León, 1848-1910 - Mora-Torres, Juan, 1956- (Book collections on Project MUSE., 2001)
The issues that dominate U.S.-Mexico border relations today - integration of economies, policing of boundaries, and the flow of workers from south to north and of capital from north to south - are not recent developments. In this insightful history of the state of Nuevo León, Juan Mora-Torres explores how these processes transformed northern Mexico into a region with distinct economic, political, social, and cultural features that set it apart from the interior of Mexico. Mora-Torres argues that the years between the establishment of the U.S.-Mexico boundary in 1848 and the outbreak of the Mexican Revolution in 1910 constitute a critical period in Mexican history. The processes of state-building, emergent capitalism, and growing linkages to the United States transformed localities and identities and shaped class formations and struggles in Nuevo León. Monterrey emerged as the leading industrial centre and home of the most powerful business elite, while the countryside deteriorated economically, politically, and demographically. By 1910, Mora-Torres concludes, the border states had already assumed much of their modern character: an advanced capitalist economy, some of Mexico's most powerful business groups, and a labour market dependent on massive migrations from central Mexico.